Method for calculating pumping characteristic of high-vacuum system with turbomolecular vacuum pump - E. V. Svichkar; N. K. Nikulin; K. E. Demihov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The pumping characteristic of a high-vacuum system depends on a number of factors: the pumping characteristics of a high-vacuum turbomolecular pump (TMN), the conductivity of connecting lines, the pumping characteristics of a for vacuum pumping system, the leakage of gas into the system, namely gas release streams, gas flows due to leakage of structural elements. The influence of these factors on the pumping characteristic of the vacuum system with TMN is considered in the work. A method for determining the parameters of a fore-vacuum pump providing an improvement in the vacuum characteristics of a vacuum system with TMN at elevated suction pressures is proposed